1984
DOI: 10.3354/meps017033
|View full text |Cite
|
Sign up to set email alerts
|

Relative importance of environmental factors in determining physiological differences between two populations of mussels (Mytilus edulis)

Abstract: Mussels Mytilus edulis were reciprocally transplanted between 2 environments, the Tamar estuary (south-west England) and Swansea dock (south Wales). Physiological and cellular responses of native and transplanted mussels at each site were measured at the beginning (January, 1978) and after 7, 16 and 23 wk. Tissue concentrations of some metals (Cd, Cu, Fe, Pb, Zn) and hydrocarbons were determined. Changes in metal and hydrocarbon concentrations in the tissues were complex and a function of specific contaminant,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(48 citation statements)
references
References 37 publications
3
45
0
Order By: Relevance
“…Feeding conditions can modify the physiological traits of mussels (Bayne et al, 1984, Bayne et al, 1987) and the differences may persist for several months, as suggested in transplantation experiments (Widdows et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Feeding conditions can modify the physiological traits of mussels (Bayne et al, 1984, Bayne et al, 1987) and the differences may persist for several months, as suggested in transplantation experiments (Widdows et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Widdows et al (1984), studying two populations of M. edulis in Great Britain, concluded that the physiological differences between the populations, which were the main reasons underlying growth differences, were the result of different environmental conditions rather than genetic factors. Dickie et al (1984) and Mallet and Carver (1989) also found that site was the main factor affecting growth in Canadian mussels, and Page and Hubbard (1987) detected a close correlation between chlorophyll a and growth in M. edulis.…”
Section: Discussionmentioning
confidence: 99%
“…According to Brey (1999), this index is more or less consistent for closely related species. However, in suspension feeding bivalves food supply and/or temperature are the main factors controlling patterns of life history, whereas the genome commits the range of possible adaptations (Stearns, 1976;Widdows et al, 1984;Bayne and Newell, 1983). Hence, the attainable data of Pectinids populations (N = 134) were divided into four broad groups regarding to (i) their hypothetical longevity (estimated as 0.95 .…”
Section: Age and Growth In Aequipecten Opercularismentioning
confidence: 99%
“…Bayne & Scullard, 1977;Widdows, 1978b;Kautsky & Wallentinus, 1980;Widdows et al, 1984). For mussels with 1 gdw, O/N < 30 is generally considered indicative of a stressed condition, since the protein catabolism is high; while O/N>50 is indicative of nitrogen saving, catabolism of carbohydrates and lipids at a level above maintenance (Widdows, 1978b).…”
Section: Schliiter and S B Josefsenmentioning
confidence: 99%